The role of the UNSC in combating the financing of terrorism in North, West and East Africa - Booyse-Mofokeng, Anneline (My University, 2016)
The manifestation of terrorism on the African continent has increasingly become a major emerging and evolving security concern. Based on the number of incidents happening on the continent, it is evident that the approach in addressing this phenomenon needs to be rethought, restrategised and redesigned in order to maximise the effect of current counter interventions by different organisations. At the centre of terrorism is the financing thereof. The bulk of this study will focus on the financing of terrorism and how the United Nations Security Council respond to it focussing on North, West and East Africa. Results should not just address the challenges of the current environment, but should be able to stand the test of time and ensure that these horrific activities do not re-occur. In order to reach this stage, it is critical that all role-players, stakeholders and organisations work together to ensure that the crisis is addressed in the most effective way, but also, critically, managed under the umbrella of an organisation that has the capability, resources, capacity and leadership to intervene in these situations successfully. The United Nations Security Council is the one organisation that can fulfil this role.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in 33% fulfilment of the requirements for the Degree of Master of Management (in the field of Security) 23 March 2016
Keywords: Terrorism--Africa--Prevention; Terrorism--Finance--Prevention; Peacekeeping forces--Africa